Promises of the Civil Society - Franz Hamburger; Eva Stauf; Felicia Lauer (Social Work & Society, 2007)
The European integration process mainly consists of the development of a European Single Market. Its political regulation is contradictory and conflicting as it is managed by a committee of the governments which - on a different level - operate against each other as representatives of competing nations. Beyond market and states the national citizens expect a culture of consent-orientated acknowledgement from a European civil society. This expectation has been very distinct in those countries which joined the European Union in 2004. In this contribution results are reported from a survey on representatives of Middle and East European networks of social work. They had been questioned about their experiences with aspects of the eastward expansion of the EU. It becomes apparent that the promises of the civil society are overdone and that it comes down to a balance of civil liberty, welfare state and the self-regulation of the civil society.